Dopamine - A preventive agent for mesenteric ischemia and reperfusion injury in abdominal compartment syndrome - (:unkn) unknown (My University, 2011)
Objectives. Acutely increased intra-abdominal pressure (IAP) may lead to abdominal compartment syndrome (ACS) and multiple organ failure. In a prospective randomized way, the effect of dopamine infusion (3 μg/kg/min) on mesenteric perfusion, cytokine levels and intestinal histopathological changes were studied in the presence of ACS. Material and Methods. The study involved 28 male Sprague Dawley rats randomly assigned to four groups (n = 7). The external jugular vein was cannulated for infusions. In group 1, before increasing IAP, a 60-minute infusion of dopamine was performed; following this, IAP was raised and the dopamine infusion was continued for another 60 minutes. In group 2 an IAP of 20 mm Hg was maintained for 60 minutes by air insufflation. In group 3, a dopamine infusion was performed simultaneously with an IAP of 20 mm Hg for 60 minutes. Group 4 was the control. Following this phase, midline laparatomy and superior mesenteric artery (SMA) dissection was carried out in all groups and SMA perfusion was measured continuously for 30 minutes with a Doppler probe. Myeloperoxidase (MPO) activity, lipid peroxidation and glutathione (GSH) levels were measured in tissue samples and histopathological scoring was carried out. Results. The results demonstrated that SMA blood flow was increased in Group 1 and Group 3 (100.77 ± 2.94 and 93.82 ± 4.91 mm Hg, respectively) but decreased significantly in Group 2 (74.23 ± 3.01 mm Hg; p < 0.01). Intestinal tissue malondialdehyde (MDA) levels (24.03 ± 2.75 nmol/g) and MPO activity (260.5 ± 11 u/g) were elevated in Group 2; histological scores were elevated in all groups (p < 0.05); and GSH levels were reduced in Group 2 (0.58 ± 0.24 μmol/g; p < 0.01). Conclusions. The results indicated that high IAP causes oxidative organ damage and that dopamine may lessen reperfusion-induced oxidative damage by reducing splanchnic perfusion and controlling the reperfusion of the intra-abdominal organs. © Copyright by Wroclaw Medical University.
Keywords: Abdominal compartment syndrome; Blood flow; Dopamine; Ischemia/reperfusion; Superior mesenteric artery